Revisiting fatty acid-mediated antibody purification from plasma with insights into selectivity and protein integrity - Sirisak Sathorn; Garnpimol C. Ritthidej; Wanatchaporn Arunmanee (PLoS ONE, 2026)
Therapeutic antibodies play an essential role in modern biopharmaceuticals, with polyclonal antibodies (pAbs) remaining indispensable for applications such as toxin and virus neutralization. However, pAb purification is complicated by serum-derived contaminants. Selective impurity precipitation using caprylic acid (C8) or sodium caprylate (NaC8) provides an effective strategy for obtaining high-purity antibody preparations and serves as a low-cost, scalable non-chromatographic alternative. However, the influence of fatty acid chain length and ionic form on differential precipitation remains poorly understood. Here, we systematically evaluated free fatty acids with varying chain length (C8–C10) and their corresponding sodium salts for pAb purification. Using model proteins, free fatty acids exhibited greater selectivity than their salt forms, and precipitation efficiency decreased with increasing chain length (C8 > C9 > C10). Importantly, C9 at 2% (v/v) provided a favorable balance between impurity removal and γ-globulin retention, achieving effective depletion of albumin while minimizing antibody loss relative to conventional C8 precipitation. Multi-spectroscopic analyses confirmed that γ-globulin maintained its native structure following fatty acid–based precipitation. When applied to the fractionation of IgG from hyperimmunized equine plasma, C9 achieved impurity reduction and IgG homogeneity comparable to conventional C8 treatment while preserving antigen-binding avidity. Collectively, these findings identify C9 as a selective and function-preserving precipitant with potential as an efficient and scalable pretreatment step in polyclonal antibody purification workflows.